Mitochondrial targeted antioxidants, mitoquinone and SKQ1, not vitamin C, mitigate doxorubicin-induced damage in H9c2 myoblast: pretreatment vs. co-treatment - Brian Sacks; Halil Onal; Rose Martorana; Amogh Sehgal; Amanda Harvey; Catherine Wastella; Hafsa Ahmad; Erin Ross; Adona Pjetergjoka; Sachin Prasad; Robert Barsotti; Lindon H. Young; et al. (BMC, 2021)
Abstract Background Preconditioning of the heart ameliorates doxorubicin (Dox)-induced cardiotoxicity. We tested whether pretreating cardiomyocytes by mitochondrial-targeted antioxidants, mitoquinone (MitoQ) or SKQ1, would provide better protection against Dox than co-treatment. Methods We investigated the dose-response relationship of MitoQ, SKQ1, and vitamin C on Dox-induced damage on H9c2 cardiomyoblasts when drugs were given concurrently with Dox (e.g., co-treatment) or 24 h prior to Dox (e.g., pretreatment). Moreover, their effects on intracellular and mitochondrial oxidative stress were evaluated by 2,7-dichlorofluorescin diacetate and MitoSOX, respectively. Results Dox (0.5-50 μM, n = 6) dose-dependently reduced cell viability. By contrast, co-treatment of MitoQ (0.05-10 μM, n = 6) and SKQ1 (0.05-10 μM, n = 6), but not vitamin C (1-2000 μM, n = 3), significantly improved cell viability only at intermediate doses (0.5-1 μM). MitoQ (1 μM) and SKQ1 (1 μM) significantly increased cell viability to 1.79 ± 0.12 and 1.59 ± 0.08 relative to Dox alone, respectively (both p < 0.05). Interestingly, when given as pretreatment, only higher doses of MitoQ (2.5 μM, n = 9) and SKQ1 (5 μM, n = 7) showed maximal protection and improved cell viability to 2.19 ± 0.13 and 1.65 ± 0.07 relative to Dox alone, respectively (both p < 0.01), which was better than that of co-treatment. Moreover, the protective effects were attributed to the significant reduction in Dox-induced intracellular and mitochondrial oxidative stress. Conclusion The data suggest that MitoQ and SKQ1, but not vitamin C, mitigated DOX-induced damage. Moreover, MitoQ pretreatment showed significantly higher cardioprotection than its co-treatment and SKQ1, which may be due to its better antioxidant effects.